Investigating surface topology and cyclic‐RGD peptide functionalization on vascular endothelialization. Issue 2 (16th September 2013) - McNichols, Colton; Wilkins, Justin; Kubota, Atsutoshi; Shiu, Yan T.; Aouadi, Samir M.; Kohli, Punit
Abstract The advantages of endothelialization of a stent surface in comparison with the bare metal and drug‐eluting stents used today include reduced late‐stent restenosis and in‐stent thrombosis. In this article, we study the effect of surface topology and functionalization of tantalum (Ta) with cyclic‐(arginine‐glycine‐aspartic acid‐d‐phenylalanine‐lysine) (cRGDfK) on the attachment, spreading, and growth of vascular endothelial cells. Self‐assembled nanodimpling on Ta surfaces was performed using a one‐step electropolishing technique. Next, cRGDfK was covalently bonded onto the surface using silane chemistry. Our results suggest that nanotexturing alone was sufficient to enhance cell spreading, but the combination of a nanodimpled surfaces along with the cRGDfK peptide may produce a better endothelialization coating on the surface in terms of higher cell density, better cell spreading, and more cell–cell interactions, when compared to using cRGDfK peptide functionalization alone or nanotexturing alone. We believe that future research should look into how to implement both modifications (topographic and chemical modifications) to optimize the stent surface for endothelialization. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 532–539, 2014.